Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay Pada Perusahaan Manufaktur Periode 2016-2020 - Kintan Ndaru Ayu Arianto; Hero Priono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Audit reports are important for stakeholders and management. For management, it is required to submit financial reports that are in accordance with financial accounting standards and have been audited by a public accountant registered with BAPEPAM. The issuance of financial reports will expedite the process of publishing financial statements. As for the timeliness of the publication of financial reports to be published, it will affect the timeliness of decision making. The purpose of this study was to determine and analyze the effect of company size, solvency, profitability, and audit committee on audit delay. The company population is all manufacturing companies in 2016-2020 and the research sample is 10 companies. The data used is secondary data in the form of financial report documentation and company annual reports obtained from the IDX. The results of the study, namely partially, show that the variables that influence audit delay are company size and profitability (ROA). The significance level of these variables is 0.022 and 0.034. While the solvency and audit committee variables have no effect. The test results simultaneously show that all variables have a significant effect on audit delay.